2008
DOI: 10.1136/adc.2007.128421
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of visual development in non-syndromic craniosynostosis: a 1-year pre- and post-surgical study

Abstract: Abnormalities of visual function were not frequent in infants with non-syndromic craniosynostosis who underwent surgical correction. Approximately half of the patients had some visual abnormalities before surgery, which subsequently improved, showing a delayed visual maturation rather than persistent abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
2
19
1
2
Order By: Relevance
“…[25] Although surgery can correct orbital asymmetry, the trochlea may remain asymmetric and ocular muscle dysfunction and subsequent vision abnormalities may persist. [26] Our findings, however, suggest that these potential vulnerabilities do not necessarily produce measurable impairments in visual perception at school age. We observed group differences primarily in fine motor ability and particularly in bimanual dexterity, with fewer meaningful differences in visual-motor integration or visual perception without a motor component (i.e.…”
Section: Discussionmentioning
confidence: 53%
“…[25] Although surgery can correct orbital asymmetry, the trochlea may remain asymmetric and ocular muscle dysfunction and subsequent vision abnormalities may persist. [26] Our findings, however, suggest that these potential vulnerabilities do not necessarily produce measurable impairments in visual perception at school age. We observed group differences primarily in fine motor ability and particularly in bimanual dexterity, with fewer meaningful differences in visual-motor integration or visual perception without a motor component (i.e.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, the trochlea is displaced for the orbital rotation and relative recession of the frontal process in UCS, causing a change in the angle through which the superior oblique turns, creating a mechanical disadvantage for its action [ 15 ]. Some studies have reported a predominance of esotropia (60–100%) [ 4 , 16 18 ] and exotropia (36%) [ 19 ] in their patient populations. Our paper is the first to discuss MED in UCS; strabismus surgery must be performed after craniofacial reconstruction because reducing intracranial pressure is the most important treatment for saving lives.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 studies report on ocular abnormalities in the various types of nonsyndromic craniosynostosis and both concern small patient groups, as shown in Tables 10 and 11 . 255 , 284 The 29 patients reported by Vasco 284 had no refractive errors and all 29 had normal vision 12 months postoperatively. The most frequent abnormality found 12 months postoperatively was strabismus in patients with unicoronal craniosynostosis.…”
Section: Vision Refraction and Motility Abnormalitiesmentioning
confidence: 98%